Selected parameters of anaerobic capacity among playersin various positions on the Polish Superleague handball team - Krawczyk, K.; Slowak, M. (Journal of Kinesiology and Exercise Sciences, 2018)
Abstract Introduction: An overview of the literature on the subject of handball indicates that today`s top-level handball is dominated by sequences of short-duration (5 - 20 seconds) intensive anaerobic physical effort. Taking into account this data and the lack of scientific contribution describing the levels of the anaerobic capacity of top-level handball players, it seems essential to research this sphere of capacity in men`s Superleague teams. Aim: The objective of the study is to evaluate the relative mechanical work (J/kg), peak power (W/kg), peak power production time (s) and peak power sustainment time (s) in Wingate tests performed on players in various positions. Basic procedures: Research participants: 18 players in the Superleague handball team; average age of participants = 25.96±3.97 years old, average height = 192.76±7.21 cm, average body mass = 97.61±11.46 kg; average BMI = 25.84±1.92. The evaluation of anaerobic capacity was performed according to the 30-second Wingate test procedure, with the use of the Monark 824E cycle ergometer and the MCE v5.0 computer software. Results: The mean peak power of the research participants was 11.12±0.84 W/kg; mean work value - 254.56±16.92J/kg, mean peak power production time - 4.82±0.82s; peak power sustainment time - 2.98±1.04s; fatigue index - 25.82±3.64%. Conclusions: In the process of top-level handball training, it is necessary to pay more attention to the development of anaerobic endurance through the increased use of interval workload.